2012
DOI: 10.1155/2012/852835
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Amoebic Liver Abscess for Clinicians in a Nonendemic Setting

Abstract: Amoebic liver abscess (ALA) is an uncommon but potentially life-threatening complication of infection with the protozoan parasite Entamoeba histolytica. E histolytica is widely distributed throughout the tropics and subtropics, causing up to 40 million infections annually. The parasite is transmitted via the fecal-oral route, and once it establishes itself in the colon, it has the propensity to invade the mucosa, leading to ulceration and colitis, and to disseminate to distant extraintestinal sites, the most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
90
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 25 publications
1
90
0
5
Order By: Relevance
“…8 ALA is widely distributed throughout the tropics and subtropics, causing up to 40 million infections annually. 9 The extent of liver abscess has remained unclear because of the lack of a population-based study. A recent previous report in Taiwan showed that PLA was endemic and that some factors including diabetes, malignancy, renal disease, and pneumonia were associated with a higher risk for the disease.…”
Section: Introductionmentioning
confidence: 99%
“…8 ALA is widely distributed throughout the tropics and subtropics, causing up to 40 million infections annually. 9 The extent of liver abscess has remained unclear because of the lack of a population-based study. A recent previous report in Taiwan showed that PLA was endemic and that some factors including diabetes, malignancy, renal disease, and pneumonia were associated with a higher risk for the disease.…”
Section: Introductionmentioning
confidence: 99%
“…It was therefore surprising to note that liver enzyme assays did not show any major variation in the study group and were globally in accordance with a cholestasis syndrome. These markers have scarcely been reported in previous amoebic disease studies (Wuerz et al, 2012). The results concerning α-2-macroglobulin were more questionable, since this biomarker is usually implicated in the regulation of liver fibrosis mechanisms.…”
Section: Discussionmentioning
confidence: 87%
“…Significant immigration flows and frequent foreign travel mean that the biological diagnosis of this condition has become an important concern in healthcare centres. Biochemical and cytological biomarkers have been uninformative thus far (Stanley, 2003;Wuerz et al, 2012), and serological tests are not compatible with an emergency context. Practitioners need tests that are quick and easy to perform, in order to guide the aetiological diagnosis in cases of strong presumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is most prevalent in developing countries and tropical areas with poor sanitary conditions due to its fecal oral spread. Risk factors also include recent travel to endemic areas, poor hygiene, low socioeconomic status and institutionalization [2].…”
Section: Introductionmentioning
confidence: 99%